2019
DOI: 10.1002/jmv.25542
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of rotavirus genotypes in the postvaccine introduction era in Ashaiman, Greater Accra Region, Ghana, 2014‐2016

Abstract: Group A Rotaviruses (RVAs) are the most important etiological agents of acute gastroenteritis (AGE) in children less than 5 years of age. Mortality resulting from RVA gastroenteritis is higher in developing countries than in developed ones, causing a huge public health burden in global regions like Africa and South‐East Asia. This study reports RVA genotypes detected in Ashaiman, Greater Accra Region, Ghana, in the postvaccine introduction era for the period 2014‐2016. Stool samples were collected from childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…As of January 2022, 114 countries (including 79% of those from Africa) have introduced RV vaccination services [4,6]. In fact, a systematic review on the impact of immunization programs in sub-Saharan Africa demonstrated that the inclusion of RV1 and RV5 vaccines led to significant reductions in the proportion of positive cases in these regions from 42% (95% CI [38][39][40][41][42][43][44][45][46] (pre-vaccination period) to 21% (95% CI 17-25) [7].…”
Section: Introductionmentioning
confidence: 99%
“…As of January 2022, 114 countries (including 79% of those from Africa) have introduced RV vaccination services [4,6]. In fact, a systematic review on the impact of immunization programs in sub-Saharan Africa demonstrated that the inclusion of RV1 and RV5 vaccines led to significant reductions in the proportion of positive cases in these regions from 42% (95% CI [38][39][40][41][42][43][44][45][46] (pre-vaccination period) to 21% (95% CI 17-25) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, at present, little is known about the molecular evolution of specific RVA genotypes. The two licensed vaccines both include the G1 genotype, and G1 still remains a largely dominant G genotype worldwide [ 12 , 13 , 14 ]. It was also reported that G1 was the predominant shedding vaccine-related viral particle in vaccines [ 15 , 16 ], which may have an effect on the evolution of wild-type G1 circulating in populations.…”
Section: Introductionmentioning
confidence: 99%